Ответ:
=================================
Пошаговое объяснение:
1.
одз:x>4
log(2)(x-4)<log(2)(32)
x-4<32
x<36
x€(4;36)
2.
одз:x>1
log(2)(x-1)>=log(2)(128)
x-1>=128
x>=129
x€[129;+беск.)
3.
одз:x<7/5
log(8)(7-5x)<log(8)(8^6)
7-5x<8^6
x>(7-8^6)/5
x€( (7-8^6)/5;7/5 )
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
=================================
Пошаговое объяснение:
1.
одз:x>4
log(2)(x-4)<log(2)(32)
x-4<32
x<36
x€(4;36)
2.
одз:x>1
log(2)(x-1)>=log(2)(128)
x-1>=128
x>=129
x€[129;+беск.)
3.
одз:x<7/5
log(8)(7-5x)<log(8)(8^6)
7-5x<8^6
x>(7-8^6)/5
x€( (7-8^6)/5;7/5 )